PENGENDALIAN PERSEDIAAN DENGAN MENGGUNAKAN METODE ECONOMY ORDER QUANTITY PADA DISTRIBUTOR MAKANAN: PENGENDALIAN PERSEDIAAN DENGAN MENGGUNAKAN METODE ECONOMY ORDER QUANTITY PADA DISTRIBUTOR MAKANAN - Zahirah, Sakinah Hassanah; Arista, Anggia (Computer Science and Industrial Engineering, 2019)
PT. Tanindo Sentosa is a company engaged in the distribution of food and beverages. In running its business, merchandise inventory at PT. Tanindo Sentosa has not been planned well so that the buying and selling process is not going smoothly. This is due to the lack of inventory of merchandise in the warehouse. The product under study was the Yummy Natural Plan Yogurt size of 1kg, 2.5kg and 500gr. This research was conducted with the aim of finding out the optimal merchandise inventory, knowing the safety stock and reorder points. Inventory control can be done using the Economic Order Quantity (EOQ) method. EOQ is a calculation of determining the optimal order quantity with a predetermined frequency and when to order again. The results showed that the EOQ method was more efficient than company calculations. The results obtained by the purchase of merchandise merchandise Yummy Natural Plan Yogurt size 1 kg, 2.5 kg and 500gr for the period May 2018 - April 2019 the most optimal according to the EOQ method for 1 kg of Yogurt size is 798 pcs with a frequency of purchase 7 times, Yogurt size 2.5 kg is 482 pcs with a purchase frequency of 10 times and Yogurt 500gr size is 407 pcs with a purchase frequency of 4 times. The results showed that if using the EOQ method the company could find out the optimal number of merchandise orders.